Cytochrome P450-induced backbone rearrangements in terpene biosynthesis of plants - Frey, Maximilian; Jochimsen, Christina Marie; Degenhardt, Jörg (Molecules, 2025)
Terpenes, the largest class of plant specialized products, are built from C5 building blocks via terpene synthases and oxidized by cytochrome P450 enz...
Gesehen am 19.01.2026